FRAUD DETERMINANTS MODERATED BY INDIVIDUAL MORALITY - Paramita, Patricia Dhiana; Luhgiatno, Luhgiatno; Adhi, Daniel Kartika; Nurkholik, Nurkholik; Wahyuningsih, Panca (STIE Pelita Nusantara Semarang, 2024)
This study took the object in the Public Accounting Firm (KAP) in Semarang City, where there is a phenomenon of increasing fraud intensity among public accountants which is motivated by increasing pressure, opportunity and rationalization among them. The purpose of this study is to determine the impact of pressure, opportunity and rationalization partially and simultaneously on fraud, to find out whether individual morality strengthens the impact of pressure, opportunity and rationalization partially on fraud. The population of the study was 140 people and the sample taken was 125 people using the Proportional Purposive Sampling technique and the data analysis technique using Moderated Regression Analysis (MRA). The results of the study can be described that pressure, opportunity and rationalization partially and simultaneously have a significant positive impact on fraud. In addition, individual morality strengthens the impact of pressure, opportunity and rationalization partially on fraud. The policy that must be taken by the management of the Public Accounting Firm (KAP) in Semarang is to make policies that can eliminate the occurrence of pressure, opportunity and rationalization in the work environment of public accountants.